Nanostructured Lipid Carrier (NLC) as a Topical Drug Delivery System : A Review - Luluk Latifah; Esti Hendradi; Dewi Isadiartuti (Sanata Dharma University, 2024)
Nanostructured Lipid Carrier (NLC) appears as the next generation of lipid nanoparticles which overcomes the weaknesses of Solid Lipid Nanoparticles (SLN). NLC is a delivery system that offers several advantages, such as significantly improved entrapment efficiency, reduced drug expulsion during long-term storage, and increased contact between the drug and the stratum corneum, thereby enhancing drug penetration. The methods used to manufacture NLC have high energy-required such as high-pressure homogenization and high shear homogenization, low energy-required such as microemulsification and phase inversion, and very low or no energy-required such as solvent evaporation and solvent injection. The basic components of an NLC are solid lipids, liquid lipids, and surfactants or mixtures of surfactants. This narrative review refers to several previously published databases on the types, preparation methods, and physical properties of NLC. This review focuses on descriptions related to the NLC as a topical drug delivery system.